1999
DOI: 10.1038/sj.onc.1203169
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal truncation of Dlk/ZIP kinase leads to abrogation of nuclear transport and high apoptotic activity

Abstract: Dlk (also termed ZIP kinase) is a novel serine/threonine kinase with a unique C-terminal domain that is rich in arginine and contains three putative NLS motifs and a functional lecuine zipper. Dlk is indeed localized in the nucleus where it shows a speckled distribution. To elucidate the biological functions of Dlk, we wanted to identify the signals relevant for nuclear transport and further the nuclear structures which Dlk binds to. Expression of various deletion and point mutations of Dlk as GFP fusion prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 36 publications
5
57
0
Order By: Relevance
“…It has been thought that murine ZIP kinase is involved in apoptosis since overexpression of active ZIP kinase but not its inactive form induces apoptosis. Consistent with the proposed role of ZIP kinase in apoptosis, it has been shown that murine ZIP kinase predominantly localizes in the nucleus [3]. On the other hand, it was found that human ZIP kinase is predominantly localized in cytosol [4], suggesting a physiological role of ZIP kinase through the phosphorylation of its cytoplasmic substrates.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…It has been thought that murine ZIP kinase is involved in apoptosis since overexpression of active ZIP kinase but not its inactive form induces apoptosis. Consistent with the proposed role of ZIP kinase in apoptosis, it has been shown that murine ZIP kinase predominantly localizes in the nucleus [3]. On the other hand, it was found that human ZIP kinase is predominantly localized in cytosol [4], suggesting a physiological role of ZIP kinase through the phosphorylation of its cytoplasmic substrates.…”
Section: Introductionsupporting
confidence: 60%
“…Initially nuclear localization of rodent ZIP kinase was reported in association with cell death inducing activity [3]. Subsequently, human ZIP kinase was cloned from Hela cells [5], which also induces cell death in Hela cells and showed essentially cytoplasmic localization.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants of ZIPK with deletion of residues 275-333 were constructed by fusion of N-and C-terminal parts of ZIPK, which were generated by PCR using terminal primers (Ko¨gel et al, 1999) and the following internal primers: 333-fw. 5 0 -ccggaattcgctgcgcgagctgcagcggg-3 0 and 275-rev.…”
Section: Plasmidsmentioning
confidence: 99%
“…In these contexts, ZIPK seems to function primarily as a myosin light chain kinase or, during mitosis, as a histone kinase (for reviews and references, see Ko¨gel et al, 2001;Haystead, 2005;Scheidtmann, 2007). A role of ZIPK in transcription is supported from its interactions with transcription and splicing factors ATF4, AATF and CDC5 (Kawai et al, 1998;Page et al, 1999a, b;Engemann et al, 2002), and its colocalization with PML bodies (Ko¨gel et al 1999;Kawai et al, 2003). Recently, ZIPK was shown to interact with STAT3 and to enhance STAT3-mediated transcription in an interleukin-6-dependent manner (Sato et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This growing list includes PKCd (Ghayur et al, 1996), PKCm (Endo et al, 2000), DAP1 (Inbal et al, 2000), PAK-2 (Rudel and Bokoch, 1997), Dlk/ZIP (Kogel et al, 1999), Etk/Bmx (Wu et al, 2001), PKN (Takahashi et al, 1998), ROCK1 (Sebbagh et al, 2001), HPK1 (Chen et al, 1999), SLK (Sabourin et al, 2000), RIP1 (Kim et al, 2000), RIP3 (Sun et al, 1999), MST1 (Ura et al, 2001) and others. It has been proposed recently that proteolytic activation of protein kinases could be a general mechanism of apoptotic signal transduction (Bokoch, 1998).…”
Section: Resultsmentioning
confidence: 99%